PENETAPAN KADAR FLAVONOID EKSTRAK TERPURIFIKASI UMBI BAWANG DAYAK (Eleutherine palmifolia (L). Merr) SECARA SPEKTROFOTOMETRI - Siti Jubaidah; Eka Siswanto; Heri Wijaya; Muhammad Putu Aditya (Jurnal Ilmiah Ibnu Sina (JIIS): Ilmu Farmasi dan Kesehatan, 2019)
Eleutherine palmifolia (L) Merr. is one of the plant that has function as medicine. One of the compound which much contained in ethanol extract of dayak union is flavonoid, so that could separate with purification. The aim of this study is to determine flavonoid levels in purified extract of dayak union root with various drying treatments using UV-Vis spectrophotometry and to find out which drying treatment that obtaine the highest flavonoid levels.Drying treatment of dayak union root simplicia were with direct sunlight for 6 hours (P1), dried by oven with temperature 60ºC for 6 hours (P2), dried by covered with black clothes (P3). Dayak union root simplicia extracted by maceratiin method using ethanol 70%, and purified step by step using n-hexane solvent. Flavonoid levels test of purified extract of dayak union root carried outby UV-Vis spectrophotometry method.The results of UV-Vis spectrophotometry obtained flavonoid levels of purified extract of dayak union root in dried by direct sunlight (P1) was 0.79%, dried by oven with temperature 60ºC (P2) was 1.57%, and dried by coveredwith black clothes (P3) was 1.02%. LSD test shows (P<0.05) the significant differences between flavonoid levels with different drying treatment.